Work-related musculoskeletal and mental health disorders: Are workplace policies and practices based on contemporary evidence?. (June 2021) - Robertson, Jennifer; Jayne, Christine; Oakman, Jodi
Highlights: We reviewed policies and practices for physical and psychosocial hazards in workplaces. Work health and safety managers lacked knowledge on psychosocial hazards. Workplace risk management policies lack comprehensive coverage of psychosocial hazards. Guidance is required to support workplaces in managing psychosocial hazards and musculoskeletal disorders. Abstract: Stress related mental health disorders (MHDs) and musculoskeletal disorders (MSDs) are significant workplace problems associated with exposure to a range of physical and psychosocial workplace hazards. Little is known about real-world risk management practices used by organisations to mitigate MHD and MSD risk. The current study examines risk management policies and practices for MHDs and MSDs in three high risk industry sectors. Method: Data was collected via interviews with 25 Work, Health & Safety (WHS) Managers from the healthcare, retail, and transport/logistics sectors on risk management practices implemented for stress related MHDs and MSDs in their organisations. The organisational policies and procedures for MHDs and MSDs were assessed for coverage of five key dimensions (reference to, exposure factors, outcomes, assessment, prevention) using an adapted policy score card. Results: Analysis of interview data identified key themes which impact risk management approaches including: a failure to adopt a comprehensive approach to risk management, and the influences of senior management. Across all three sectors, coverage of physical hazards was more comprehensive in comparison to psychosocial hazards. Conclusions: Despite recognition that MHDs and MSDs are significant workplace problems, approaches to manage these complex health issues are not based on contemporary evidence. Transactional approaches are used which fail to take account of the multiple interacting hazards associated with the development of work related MHDs and MSDs. Improved guidance material and support from the regulators is required along with education of WHS Managers about how to identify and manage psychosocial hazards to reduce the significant burden of MHD and MSDs.